Klasterisasi Peraturan Daerah di Seluruh Wilayah Jawa dengan Menggunakan Algoritma K-means - Nur Aini Rakhmawati; Deanda Bevani Aletha; Luh Putu Gayatri Widiastuti; Alexander Sidum Laka Kaki; Achmad Thoriq Aminullah (ISB Atma Luhur, 2020)
The Local Indonesian government generates various legal products. This study aims to cluster the titles of regional regulations in Java. The data are collected from law repositories of all provincial governments in Java. The repository is called as JDIH. The analytical method used is clustering with the K-means algorithm. We divide 1849 regulations into ten clusters. 890 data are in the cluster related to motor vehicle tax, public health and safety.